RosettaStone English : (Rosetta Stone, 2010)
Contents exercises to help enhance a student's learning experience. The activities in this workbook provide an opportunity for learners to practice their language skills through reading and writing exercises that reinforce the concepts covered in the Rosetta Stone software.